2014
DOI: 10.14245/kjs.2014.11.3.169
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of a Zero-profile Device Comparing with Stand-alone Cage and Anterior Cervical Plate with Iliac Bone Graft in the Anterior Cervical Discectomy and Fusion

Abstract: ObjectiveA Zero-profile device is a cervical stand-alone cage with integrated segmental fixation device. We characteristically evaluated the radiological changes as well as clinical outcomes in the application of Zero-profile devices compared with stand-alone cages and anterior cervical plates with iliac bone grafts for the cervical disease.MethodsRetrospectively, total 60 patients at least more than one year follow-up were enrolled. Twenty patients were treated with Zero-profile devices (Group A), twenty pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…Three studies were excluded because there were no events data[16, 17, 26]. The fixed-effects model was applied to compare the dysphagia rate at the end of follow-up between the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were excluded because there were no events data[16, 17, 26]. The fixed-effects model was applied to compare the dysphagia rate at the end of follow-up between the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…None of the individuals had dysphagia after 3 months postoperatively (33). A zero-profile device is thought as a valuable alternative for ACDF with a low incidence of postoperative dysphagia and without segmental kyphotic change (34). Cho et al found that the zero-profile anchored spacer has some advantage over stand-alone PEEK cage for maintaining segmental lordosis and lowering subsidence rate after single level ACDF (35).…”
Section: Discussionmentioning
confidence: 99%
“…Although anterior cervical cage-plate has been reported to provide stability and reduce complications related to the use of stand-alone cage, the application of plate induced some complications, such as dysphagia, esophageal injury, and looseness of screws3720). Dysphagia is the common complication after ACDF using plate.…”
Section: Discussionmentioning
confidence: 99%